MAPPING THE POTENTIAL DISTRIBUTION OF FLOOD DISASTERS IN THE CITY OF SUNGAI PENUH USING ARCGIS - Ritongan, D. M. Magdalena; Anggi Deliana S, Anggi; Dewi, Ira Kusuma; Simbolon, Raja P; Nawangsari, Dhinda Ayu; Sandy, Bima Kurnia (JOURNAL ONLINE OF PHYSICS, 2025)
This study aims to map the potential distribution of flooding in Sungai Penuh City by utilizing Geographic Information System (GIS) technology using ArcGIS software. The analysis was conducted by integrating several key parameters that influence flooding, namely rainfall, slope, soil type, land use, and proximity to rivers. Each parameter was reclassified and weighted based on its level of influence on flood potential, then a Weighted Overlay analysis was performed to produce a flood vulnerability zoning map. The results showed that the area with the highest flood vulnerability was in the central part of Sungai Penuh City, which has relatively flat topography, high rainfall intensity, and is a densely populated residential area crossed by several rivers. Meanwhile, the northeastern part and areas with steep slopes showed lower vulnerability levels. The resulting flood vulnerability map can be used as a reference in spatial planning, disaster mitigation, and sustainable land resource management in Sungai Penuh City.